Nationwide survey of physicians’ familiarity and awareness of diabetes guidelines in China: a cross-sectional study - Bing Yan; Shu-Yu Yang; Jian-Ping Liu; Le Li; Na Zhan; Li-yan Jia; Cao-xin Huang; Neng-jiang Zhao; Bao-yong Lai; Zhi-hai Zhang; Yuan-bing Lin; Miao-na Cai; et al. (BMJ Open)
Objective This study aims to investigate physicians’ familiarity and awareness of four diabetes guidelines and their practice of the recommendations outlined in these guidelines.Design A cross-sectional study.Setting An online questionnaire survey was conducted among physicians affiliated with the Specialist Committee for Primary Diabetes Care of China Association of Chinese Medicine, using the snowball sampling method to ensure a broader representation of physicians.Participants 1150 physicians from 192 cities across 30 provinces in China provided complete data.Results Tertiary care hospital physicians (TCPs) exhibited the highest familiarity with the Guideline for the Prevention and Treatment of Type 2 Diabetes Mellitus in China (91.3%), followed by the National Guidelines for the Prevention and Control of Diabetes in Primary Care (76.8%), the Standards of Medical Care in Diabetes (72.2%) and the Guidelines for Prevention and Treatment of Diabetes in Chinese Medicine (63.8%). Primary care practitioners (PCPs) exhibited familiarity with these four guidelines at about 50% or less. Self-reported reference to modern diabetes guidelines by physicians is more frequent than traditional Chinese medicine (TCM) diabetes guidelines, with rates at 73.2% and 33.8%, respectively. Approximately 90% of physicians provided instructions on self-monitoring of blood glucose to their patients with diabetes. Less than one-third of physicians referred patients to a specialised nutritionist. In terms of health education management, TCPs reported having a diabetes health management team at the rate of 75.7%, followed by secondary care hospital physicians at 57.0% and PCPs at 27.5%. Furthermore, approximately 40% of physicians did not fully grasp hypoglycaemia characteristics.Conclusions Familiarity and awareness of the screening guidelines varied among physicians in different hospital settings. Importantly, significant discrepancies were observed between physicians’ awareness and their self-reported reference to modern medicine guidelines and TCM guidelines. It is essential to consistently provide education and training on diabetes management for all physicians, particularly PCPs.